Telaah Reformasi Akuntansi Sektor Publik di Indonesia: Perspektif Luder Contingency Model - Sherly Alifah Citrayanti; Indrawati Yuhertiana (Jurnal Ilmiah Ekonomi Global Masa Kini)
This study aims to examine public sector accounting reforms in Indonesia using the perspective of the Luder Contingency Model. This study used a literature study approach, the data were taken from 61 previous studies with a research span of the last 10 years. Researchers use google scholar, emerald, and sciendirect databases. The results show that many researchers are interested in Luder's Contingency Model theory which is usually used as a basis for public sector research, especially local governments. Research conducted in the last 10 years has begun to develop out of the context of public sector accounting reforms, especially local governments, to more macro policies and outside of local government organizations such as universities and other government agencies. The research identified includes tax policy, debt policy, implementing Luder's model theory into BLUD’s such as universities, and formulating suggestions and evaluating financial reporting from the Customs and Excise agencies. Luder's Contingency Model theory rests on four assumptions of the public sector innovation process, namely stimuli, social structural variables of information users, structural variables of characteristics of political administration or producers of information, and implementation barriers. Keywords : Luder’s Contingency Model, Public sector accounting reform,  Study literature review